Avaliação dos métodos de modelagem e parametrização de dispositivos fotovoltaicos mono e multi junção - Chenche, Luz Elena Peñaranda (2015)
This work deals with the analysis applied to the main methodologies found in literature for estimating the properties related to the physical phenomena in photovoltaic devices (parametrization), as well as the most important mathematical models used in the calculation of operating electrical characteristics of these devices (characterization). These devices are related to the mono and multi-junction technologies, when they are exposed to a condition where the temperature and solar radiation vary. Therefore, four parametrization methods were shown, including three analytical, and five models of electrical characterization, where two of them are specifically for multi-junction devices. Thus, several case studies were proposed which defined different situations for comparing the performance of the methods evaluated. In this way, the procedures that best fit to each type of photovoltaic technology were identified. Finally, according to the results obtained in the parameterization, the method based on the Generalized Reduced Gradient (GRG) nonlinear algorithm showed greater accuracy for all case studies and for all photovoltaic devices. As for the characterization, the main advantages and disadvantages of all models were determined, highlighting Domínguez, et al. (2010) model, due to the highest robustness and wide application range.